Pengaruh Umur Pertama Melahirkan, Pemeriksaan Kehamilan, Penolong Persalinan Terhadap Komplikasi Persalinan di Sumatera Selatan (SDKI 2012) - Budiawan Budiawan; Slamet Widodo; Tatang Abdul Majid Sariaman (Jurnal Empirika, 2017)
Maternal Mortality Rate (MMR) in Indonesia is quite high, at 359 per 100,000 live births (IDHS 2012). AKI is an indicator of the health of mothers, especially the risk of death for pregnant women and childbirth and post-partum. Most maternal deaths occur Complications in labor and post-partum period is a direct cause of maternal deaths. The purpose of this research was to determine the effect of age at first childbirth, pregnancy tests and birth attendants to complications of childbirth in South Sumatra province. This study is an analysis of studies using secondary data obtained from Indonesia Demographic and Health Survey 2012. The study design used is cross sectional with a sample of 299 mother's age at first birth. Analysis was performed using univariate, bivariate, and multivariate logistic regression. The results of this study variables together influential variable although birth attendants did not significantly affect the incidence of complications of childbirth. From the results of analysis show that the dominant factor that influence the incidence of low birth complications age at first childbirth and pregnancy testing.Â